An Analysis of Value Chain in the Vietnam Construction Industry - Nguyen Van, Tam; Nguyen Quoc, TOAN; Le Dinh, Linh (International Journal of Sustainable Construction Engineering and Technology, 2021)
A value chain in construction industry is implemented to ensure that a construction project is successful from the planning stages, all the way to the completed and approved building. Therefore, it is important to utilize a construction value chain because it ensures that the project delivers the maximum value for the least amount of capital. However, value chain analysis in the construction industry is little understood. The present study aims to analyze the status quo for the construction value chain in Vietnam. The findings indicated that there are three primary parts of the Vietnam construction value chain. The analysis results indicated that there are three primary parts of the Vietnam construction value chain which includes: (1) input factors (i.e., labors, materials, and machines); (2) construction processes (i.e., design, bidding, foundation construction, structural construction, and finishing works); (3) construction markets (i.e., civil construction market, industrial construction, infrastructure construction). The outcomes illustrated a comprehensive picture in the Vietnam construction value chain and build a strong platform to implement better appropriate tasks towards improving sustainable competitive advantages in the construction industry.